Ekstraksi Kitin Dan Kitosan Tulang Sotong Menggunakan Teknologi Microwave - Muhammad Fakhrudin Zukhri; Putri Elvita Dewi Putri Elvita Dewi; Joshfira Eurika Widianto Joshfira Eurika Widianto; Siti Masruroh Siti Masruroh (Universitas Sains dan Teknologi Komputer, 2025)
The increasing production within the seafood processing industry has resulted in a significant rise in the volume of marine waste. A major component of this waste is chitin, which can be derived from the shells of shrimp, crabs, and other marine organisms. This offers substantial potential for processing marine waste into high-value products such as chitosan. Chitosan exhibits numerous physiological functions, including biodegradability, biocompatibility, non-toxicity, anticancer properties, lipid-lowering effects, and immune-enhancing capabilities. This study aims to extract chitin and chitosan from cuttlefish bone waste using microwave irradiation methods and to evaluate the effectiveness of microwave irradiation in improving the efficiency and quality of chitin and chitosan extraction compared to conventional methods. The extracted chitin and chitosan were analyzed and characterized using Fourier-transform infrared spectroscopy (FTIR) to identify functional groups and UV-Vis spectrophotometry. The FTIR analysis results demonstrated the successful deacetylation of chitin into chitosan. This was marked by a broad peak in the range of 3200–3500 cm⁻¹, representing the stretching vibrations of hydroxyl (-OH) and amine (-NH) groups. The peak at 2922 cm⁻¹ corresponded to C-H vibrations from methyl (-CH) and methylene (-CH₂) groups. The reduction in the intensity of the carbonyl (C=O) peak at 1650 cm⁻¹ indicated the removal of most acetyl groups, while the peak at 1560 cm⁻¹ suggested the presence of primary amine (-NH₂) groups, which are characteristic of chitosan’s structure. These findings highlight the potential of microwave irradiation as an effective method for the extraction of high-quality chitosan from marine waste, providing a sustainable solution for waste utilization in the seafood processing industry. Further investigations could explore the optimization of microwave parameters to enhance the yield and functional properties of chitosan for various applications.